Assessment of Genetic Variability and Association of Traits in French Marigold (Tagetes patula L.) Genotypes - Bhusaraddi, Priya; Bhagat, Vaishali; Kulkarni , Balaji; Cholin, Sarwamangala; Kiran, K. N. (International Journal of Bio-resource and Stress Management, 2024)
The experiment was conducted during rabi season (September, 2020–February, 2021) at Floriculture and Landscape Architecture experimental plots, University of Horticultural Sciences, Bagalkot, Karnataka, India to study the extent of genetic diversity present in the selected twenty-five genotypes for the experiment. Results obtained for heritability, genotypic coefficient of variation (GCV), phenotypic coefficient of variation (PCV) and genetic advance as percent of mean indicated higher values for majority of the traits studied in the experiment and their importance as basis for selection in the breeding program. Correlation studies for various parameters among the genotypes recorded positive and significant phenotypic and genotypic correlation with almost all the traits and non-significant and positive correlation was noticed for trait flower diameter. Phenotypic and genotypic path coefficients of flower yield with majority of other traits showed positive effects and their implications for further breeding was indicated. The outcome of genetic divergence gives scanty of genetic variability in the genotypes, except one all twenty-four were fallen in the same cluster. The Significance of selecting genotypes with a broader genetic base was helpful for future breeding programs. The study concludes that, yield is complex trait that is dependent on the other growth attributes, correlation and path studies gave the effect of different attributes on yield. Most of the traits were controlled by additive genes and therefore there is an opportunity to practice early selection in French marigold for breeding programs.